Modifikasi Permainan Olahraga Untuk Meningkatkan Minat Belajar Siswa Melalui Olahraga Tradisional - azhar, faishal saiful; Sonjaya, Azhar Ramadhana; Kosasih, Alam Hadi; Z. Arifin, Z. Arifin Ramadhana (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2025)
Objective. The purpose of this study is to determine the impact of modifications to sports games to increase student interest in learning through traditional sports.. Materials and methods. This research was conducted on 33 students of XII IPA 7 class at SMAN 6 Garut. The method used in this research is experimental method. In the research design used, this is a one group pretest posttest design. The instrument used in this study is a learning interest questionnaire which has 4 indicators: (1) enjoyment, (2) student involvement, (3) interest, (4) student attention. Results. The results showed that the students' interest in learning increased according to the pretest and posttest scores that were analyzed. The variable of students' interest in learning that has a high increase is the indicator of feeling happy, with a comparison value of the pretest value of 69 increasing to 90 on the posttest, with a difference of 21, the pretest significance value is 0.06> 0.05, therefore the value is significant, and the posttest significance value is 0.21> 0.05, then the value is also significant.. Conclusion. Based on the results of the research conducted on the modification of sports games to increase students' interest in learning through traditional sports, it can be concluded that the modification of sports games using traditional sports is significantly able to increase students' interest in learning. The modifications made were successful in creating feelings of enjoyment, increasing students' involvement, increasing students' interest in learning, and also attracting students' attention to sports learning.